Association of echocardiographic left ventricular structure and −344C/T aldosterone synthase gene variant: A meta-analysis. (December 2015) - Wang, Lijuan; Zhou, Jiapeng; Zhang, Bei; Wang, Hao; Li, Mei; Niu, Qiuli; Chen, Yubao; Chen, Runsheng; Wen, Shaojun
Background: Aldosterone synthase (CYP11B2) is one of the most studied candidate genes related to essential hypertension (EH) and left ventricular hypertrophy (LVH). Some studies have focused on the relationship between −344C/T polymorphism (rs1799998) in the CYP11B2 gene and LVH, but the results are controversial. This meta-analysis is purposed to reveal the relationship between the −344C/T and the left ventricular structure and function, including left ventricular end diastolic dimension (LVEDD), left ventricular end systolic diameter (LVESD), left ventricular mass/left ventricular mass index (LVM/LVMI), left ventricular posterior wall thickness (LVPWT), and interventricular septal wall thickness (IVS). Methods: A literature search of PubMed and Embase databases was conducted on articles published before January 27, 2014. The odds ratios with 95% confidence intervals were calculated. Heterogeneity analyses were performed using meta-regression. Tests for publication bias were also performed and biased studies should be removed from subsequent analyses. Results: There were 20 studies with a total of 6780 subjects meeting the inclusion criteria. The main finding was that concentration levels of LVEDD and LVESD were higher in CC homozygous individuals than in TT homozygous individuals in the whole group. In the Asian subgroup, TT homozygous individuals had larger IVS than CC homozygous individuals. In the Caucasian normotension subgroup, CC homozygous individuals had larger LVM/LVMI than TT homozygous individuals. In the Asian essential hypertension subgroup, TT homozygous individuals had larger LVPWT values than CC homozygous individuals. Conclusions: The present findings support the hypothesis that CC homozygous individuals may have greater left ventricular diameters (LVEDD and LVESD) regardless of their ethnicities or physical conditions.